PENGARUH MEDIA PEMBELAJARAN MICROSOFT POWER POINT TERHADAP KEMAMPUAN KOGNITIF PADA ANAK USIA DINI KELOMPOK B (5-6 TAHUN) - Nurdiyah Permata Sari; Setiyo Utoyo; Mohamad Zubaidi (Student Journal of Early Childhood Education, 2021)
The purpose of this study was to see the effect of Microsoft Power Point learning media on cognitive abilities in early childhood group B, Gorontalo City. This research is an experimental quantitative research with one group pretest-posttest research design and a sample size of 25 children. The results showed that there were differences in cognitive abilities before and after using Microsoft Power Point learning media. Judging from the average number before using Microsoft Power Point learning media is 18.04 and the average value after is 32.84. Based on the t-test using paired samples test, the results of the t-test = 23.90 while the value of t-table = 2.064, so the value of t-count = 23.90 > t- table = 2.064 or p-value = 0.00 <0.05 in other words tcount > ttable then Ho is rejected and H1 is accepted, which means that there is an influence of Microsoft Power Point learning media on cognitive abilities in early childhood. The increase is influenced because Microsoft Power Point attracts children's interest to recognize symbols, numbers, shapes, recognize colors, recognize differences from something that almost looks the same, recognize different sounds, and recognize sound sources.